Large production of cholera toxin by Vibrio cholerae O1 in yeast extract peptone water. - Iwanaga, M (1987)
A large amount of cholera toxin (CT) was produced by Vibrio cholerae O1 cultured in yeast extract-peptone water. The organisms were cultured initially in a stationary test tube (small surface-to-volume ratio) until the end of the exponential phase and subsequently cultured in a shaking flask for 15 to 20 h. By this method (previously reported as the AKI-SW method), most cholera vibrios produced an abundance of CT (up to 64 micrograms/ml), regardless of their biotype and serotype. A substantial amount of CT was produced even in basic peptone water (2% peptone, 0.5% NaCl). Use of sodium bicarbonate, which markedly stimulated CT production in the stationary test tube culture, was undesirable for CT production by the culture method used here. CT production was greatly influenced by culture conditions but was not significantly affected by the composition of the medium.